Geospatial analysis of recorded theft and robbery cases in Quezon City using geographic information systems and spatial analysis - Lanuza, Eugene Allan H.
This study examined the crime profile of Quezon City (QC) using recorded theft and robbery cases from November 2014 to November 2015. Through variable cross-referencing and hotspot mapping, temporal and spatial patterns in the crime cases were revealed, particularly the identification of Greater Lagro, Fairview, Batasan Hills, Bagong Pagasa, Bahay Toro, and Socorro as barangays of highest crime concentration, as well as the months; April, May and June, when theft and robbery incidents are least likely to transpire. In addition, the study also explored the relationship between the crime cases and the city's sociodemographic attributes (i.e. population density, unemployment rate, etc.) and spatial features (schools, malls, markets, etc.). Using regression analysis (observation units = 141 barangays of QC), specifically, ordinary least squares (OLS) and spatial lag/error; variables that are contributing to the occurrence of theft and robbery were identified. Logarithmic transformation was used in data pre-processing to improve linearity of variable relationship. Various OLS and spatial lag/error regression models with different independent variable combinations were constructed and assessed through their statistical performance, and all insignificant independent variables were eliminated. Through the final spatial error model for theft (regressors: population density, elementary schools, malls, churches, police stations, and high-rise buildings) and OLS Model for robbery (regressors; population, colleges, malls, police stations, and high-rise buildings), having R-squared (R2) values of 0.59 and 0.49 respectively; the results of the study confirmed that theft and robbery are not only a function of poverty, which is often referred to; it is also influenced by space. Certain spaces serve as the containers for objects and activities that attract offenders, that's why it is important to enhance security measures within these spaces to deter possible crime offenders.